Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1523/jneurosci.3442-17.2019
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of Recurrent Layer 5 Corticospinal Networks Following Adult Motor Training

Abstract: Recurrent synaptic connections between neighboring neurons are a key feature of mammalian cortex, accounting for the vast majority of cortical inputs. Although computational models indicate that reorganization of recurrent connectivity is a primary driver of experiencedependent cortical tuning, the true biological features of recurrent network plasticity are not well identified. Indeed, whether rewiring of connections between cortical neurons occurs during behavioral training, as is widely predicted, remains u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 66 publications
0
21
1
Order By: Relevance
“…Both motor learning and running wheel exercise might thus shape task-related activity in neuronal ensembles of layer II/III motor cortex, leading to activation of layer V neurons via intracortical connections. In line with this idea, a recent study showed that learning of motor tasks leads to enhanced activity of layer V pyramidal neurons (Biane et al, 2019) and that recurrent projections are involved in remodeling motor circuits. Such recurrent projections are required for motor learning and also target layer II/III neurons.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Both motor learning and running wheel exercise might thus shape task-related activity in neuronal ensembles of layer II/III motor cortex, leading to activation of layer V neurons via intracortical connections. In line with this idea, a recent study showed that learning of motor tasks leads to enhanced activity of layer V pyramidal neurons (Biane et al, 2019) and that recurrent projections are involved in remodeling motor circuits. Such recurrent projections are required for motor learning and also target layer II/III neurons.…”
Section: Discussionmentioning
confidence: 82%
“…This could be important to forward altered modes of cortical activity to striatal MSNs which undergo changes in synaptic turnover and activity in a motor task-specific manner (Sheng et al, 2019). Finally, the subpopulation of BDNF expressing neurons in layer V might also project to the spinal cord or govern corticospinal projection neurons (Biane et al, 2019). Those neurons target spinal cord interneurons and send their collaterals to the striatum (Molyneaux et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Because activation of VIP neurons can powerfully inhibit the activity of other GABAergic neurons (particularly SST neurons), it has been suggested that their primary function is disinhibition (Figure 2B), a conclusion supported by both detailed electrophysiological recordings from in vivo recordings and correlation analysis (Lee et al, 2013;Pfeffer et al, 2013;Pi et al, 2013). Indeed, experimental evidence indicates that increased VIP or suppressed SST activity is required for the increase in visual responses following monocular deprivation in adults (Fu et al, 2015), although the (Audette et al, 2019;Biane et al, 2019). It is unknown how thalamic drive to or feedforward inhibition from PV neurons changes during the early stages of sensory or motor learning (gray).…”
Section: Plasticity: a Common Feature Of Neocortical Circuitsmentioning
confidence: 94%
“…We used computational modelling to study the relationship between neural manifold and learning. As motor learning can drive network rewiring in motor cortex on a short timescale [Xu et al, 2009, Biane et al, 2019, Tavor et al, 2019, Ohbayashi, 2020, we wanted to test whether local network rewiring can account for within-manifold, as well as outside-manifold learning.…”
Section: Introductionmentioning
confidence: 99%